Analisis Pelanggaran Etika Profesi Akuntansi: Studi Kasus: PT. Asuransi Jiwasyara - Saridawati Saridawati; Imelda Cinta Chrissanty; Rachel Septya Sulistyastuti; Elvia Nur Aziza; Mart Eliany (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The professional code of ethics is an important rule for the profession which aims to improve quality and maintain the dignity of the profession. Where an accountant must uphold ethical principles so as to build trust for users of accounting services. The large amount of business competition that occurs today has led to violations of professional ethics. This violation is a very serious problem for the ethical standards of the accounting profession, one of which was a violation found at PT Asuransi Jiwasraya which manipulated its financial reports. Starting in 2006, the Ministry of BUMN and OJK stated that Jiwasraya's equity was recorded at negative IDR 3.29 trillion. In December 2019, the Attorney General's investigation into the alleged Jiwasraya corruption case stated that there was a violation of the precautionary principle in investing. This analysis aims to explain the basic concepts of ethics, code of ethics and basic principles of accountant ethics that have been violated by PT Asuransi Jiwasraya. In this case, there were 5 basic principles of accounting ethics that were violated by PT Asuransi Jiwasraya, namely integrity, objectivity, competence and professional prudence, confidentiality and professional behavior.